How do CaO/CuO materials evolve in integrated calcium and chemical looping cycles? - Yaoyao Zheng; Stuart A. Scott (Carbon Capture Science & Technology)
Maintaining high CO2 uptake is critical for combined Ca-Cu looping applications, however, the long-term behaviour of combined Ca and Cu materials under repeated cycling conditions remains less understood. This study examined three materials with a fixed Cu/Ca mole ratio of 1.6 to analyse the material phase evolution and identify factors influencing CO2 uptake. The materials underwent 50 TGA cycles in two distinct looping applications: blast furnace gas (BFG) cycling (reduction-carbonation-oxidation) and flue gas cycling (carbonation-reduction-oxidation).Different preparation methods significantly affected the initial phase distribution. The multi-grain precipitate material (MGP), prepared to minimise the chemical contact between Ca and Cu, primarily contained separate CaO and CuO phases; while the multi-stage mechanically mixed materials (MM1 and MM2), in which there was extensive contact between the Ca and Cu, exhibited mixed Ca-Cu-O phases along with separate CuO. However, the initial phase distribution had little influence on the longer-term CO2 uptake with the accessibility of CaO and cycling conditions having a more significant impact. BFG cycling consistently resulted 70–100; % greater CO2 uptake than flue gas cycling, highlighting the strong influence of cycling conditions.